Proceedings Mekong Forum on Water, Food and Energy - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
This provides an overview of the second Mekong Hydropower Forum held in Hanoi, November 13-15, 2013.